Sintering and properties of magnesium orthosilicate ceramic. Issue 10 (December 2015) - Jeffrey Chin, K.L.; Ramesh, S.; Kelvin Chew, W.J.; Ganesan, P.; Bang, L.T.; Ching, Y.C.; Niakan, A.; Tan, C.Y.; Purbolaksono, J.; Teng, W.D.
Abstract: In the present work, magnesium orthosilicate powder of high purity and crystallinity was successfully synthesized from precursors of talc and magnesium oxide via solid state reaction through combined steps of 3 h ball mill and annealing at 1400 °C for 1 h. The effects of ultrasonication, ball milling and annealing on the mixture of precursors were examined with regards to forsterite (Mg2 SiO4 ) phase formation. Ultrasonication of higher intensity and longer ball mill duration led to reduction in intensity but not total elimination of secondary peaks of enstatite and MgO in the powder. Sintering properties were compared for magnesium orthosilicate prepared from two methods i.e. powder mixture which was ball mill for 3 h and annealed at 1400 °C (Type 1) with that which was ball mill for 3 h only (Type 2). It was found that the Type 2 powder exhibited superior densification rate as well as remarkable high hardness (7.7 GPa) and fracture toughness (5.16 MPa m 1/2 ) when compared to the Type 1 sintered samples. Despite achieving poorer density, the Type 1 samples exhibited higher elastic modulus without incurring any significant grain growth.